2005
DOI: 10.1182/blood-2004-07-2697
|View full text |Cite
|
Sign up to set email alerts
|

Autoantigens signal through chemokine receptors: uveitis antigens induce CXCR3- and CXCR5-expressing lymphocytes and immature dendritic cells to migrate

Abstract: We tested the hypothesis that interaction between autoantigens and chemoattractant receptors may be an important step in the development of autoimmunity. The retinal autoantigens S-antigen (S-Ag) and interphotoreceptor retinoid binding protein (IRBP) can induce autoimmune uveitis in rodent models. We evaluated the chemotactic activity of S-Ag and IRBP and found that both induced migration of human and mouse immature dendritic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
38
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 42 publications
0
38
0
Order By: Relevance
“…Studies with several autoantigens (ie, histidyl-transfer RNA synthetase, retinal S-antigen, etc) have demonstrated that these autoantigens can initiate an innate immune response and, in sensitive individuals, adaptive immune response by attracting iDCs and T and B cells expressing chemokine receptors. 48 Although the precise (patho)physiologic role of PR3 in the immunopathogenesis and/or autoimmune reaction of WG has yet to be established with certainty, our data suggest that the proteolytic activation of PAR2 on DCs represents a new avenue in the direction to understand the early pathogenic events in WG: DCs can become stimulated to mature by PR3 released by damaged cells through the PAR-2 signaling pathway. These PR3-maturated DCs become fully competent APCs for the stimulation of autoreactive Th1-type CD4 ϩ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with several autoantigens (ie, histidyl-transfer RNA synthetase, retinal S-antigen, etc) have demonstrated that these autoantigens can initiate an innate immune response and, in sensitive individuals, adaptive immune response by attracting iDCs and T and B cells expressing chemokine receptors. 48 Although the precise (patho)physiologic role of PR3 in the immunopathogenesis and/or autoimmune reaction of WG has yet to be established with certainty, our data suggest that the proteolytic activation of PAR2 on DCs represents a new avenue in the direction to understand the early pathogenic events in WG: DCs can become stimulated to mature by PR3 released by damaged cells through the PAR-2 signaling pathway. These PR3-maturated DCs become fully competent APCs for the stimulation of autoreactive Th1-type CD4 ϩ T cells.…”
Section: Discussionmentioning
confidence: 99%
“…The number of cells that migrated to the lower surface was microscopically counted at six randomly chosen high-power fields. IFN-g inducible protein 10 (IP10), previously described, was used as a control, as immature dendritic cells exhibit significant chemotaxis through CXCR3 (28,29). Three replicates were done for each treatment and the experiment was done thrice.…”
Section: Methodsmentioning
confidence: 99%
“…34 Because of its pertussis toxin sensitivity, probably the CXCR3A variant, and not CXCR3B, is activated by CXCL4L1 on human leukocytes. Indeed, earlier reports indicated the presence of CXCR3 on DCs, 35,36 NK cells, 37 and activated T cells. 38 .…”
Section: Cxcl4l1 Uses Cxcr3 For Angiostasis and Chemotaxis 485mentioning
confidence: 99%